Psychometric Model of College Students Based on Time Series Analysis and Its Application in Educational Management - Lu Lu (Hindawi-Wiley, 2022)
The psychological measurement method of college students is a hot issue in the field of educational management research. Based on the time series analysis theory, this paper constructs a psychological measurement model for college students. This paper analyzes the psychometric behavior data, uses the time series analysis method for behavior prediction, deeply mines the relevant component information of the psychometric data, and solves the problems of weak correlation between the functions of the psychometric platform and low data accuracy of the psychometric model. At the same time, taking the intervention target group and the intervention mode as the basic variables of the intervention classification system, combining these two dimensions, a two-dimensional classification framework for psychometric intervention was proposed, and four types of different psychometric intervention measures were applied. During the simulation process, a psychometric trajectory matrix was constructed, and a two-dimensional data extraction network was used to extract the psychometric pattern data of a certain period of time. The experimental results show that using the student mental state data as a label can obtain a low-coupling training set classification for psychometric effects of college students.